2022
DOI: 10.1111/1541-4337.12933
|View full text |Cite
|
Sign up to set email alerts
|

Prospection of the use of encapsulation in food packaging

Abstract: Food safety and extended shelf life linked to convenience were the major reasons for the development of the packaging field. However, advances in material science and the widespread encapsulation technologies are allowing the establishment of new concepts for packages, such as intelligent and active packages. Particulate systems have been developed in recent years for the most diverse area with several purposes that can be employed to improve packaging performance mainly focusing on the modification of barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 211 publications
0
3
0
1
Order By: Relevance
“…All of these attributes used to provide protection against degradation, volatilization or undesirable interactions with other compounds, controlled release or mask some unpleasant effects are also fundamental when developing active packaging systems through the incorporation of active compounds in the matrix. 415 Microcapsule-based systems have been developed in recent years for the diverse areas to improve packaging performance mainly focusing on the modification of barrier properties in the food packaging field. Vieira and coworkers found that carvacrol microcapsules (CMF) with higher values of thickness (0.41 AE 0.04 mm), moisture content (13 AE 1 g water/100 g film), opacity (20 AE 1%), water vapor permeability (WVP) (4.4 AE 0.4) Â 10 À10 GPa À1 s À1 m À1 , oxygen permeability (O 2 P) (1.3 AE 0.3) Â 10 À12 GPa À1 s À1 m À1 and carbon dioxide permeability (CO 2 P) (1.3 AE 0.3) Â 10 À12 GPa À1 s À1 m À1 can increase the shelf-life of refrigerated salmon to 4-7 days of storage as compared to those of the chitosan control films.…”
Section: Food and Packagingmentioning
confidence: 99%
“…All of these attributes used to provide protection against degradation, volatilization or undesirable interactions with other compounds, controlled release or mask some unpleasant effects are also fundamental when developing active packaging systems through the incorporation of active compounds in the matrix. 415 Microcapsule-based systems have been developed in recent years for the diverse areas to improve packaging performance mainly focusing on the modification of barrier properties in the food packaging field. Vieira and coworkers found that carvacrol microcapsules (CMF) with higher values of thickness (0.41 AE 0.04 mm), moisture content (13 AE 1 g water/100 g film), opacity (20 AE 1%), water vapor permeability (WVP) (4.4 AE 0.4) Â 10 À10 GPa À1 s À1 m À1 , oxygen permeability (O 2 P) (1.3 AE 0.3) Â 10 À12 GPa À1 s À1 m À1 and carbon dioxide permeability (CO 2 P) (1.3 AE 0.3) Â 10 À12 GPa À1 s À1 m À1 can increase the shelf-life of refrigerated salmon to 4-7 days of storage as compared to those of the chitosan control films.…”
Section: Food and Packagingmentioning
confidence: 99%
“…Previous studies show that microencapsulation is a technique that aims to improve the effectiveness and stability of essential oils, as well as provide controlled release over time (Barbosa et al ., 2022; Fernandes et al ., 2022). The encapsulation of EO has shown to reduce the amount of oil required for antimicrobial and/or antioxidant activities (Zanetti et al ., 2018) and unnecessary effects of plasticisation (Jaramillo et al ., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dentre os aditivos, o OE de tomilho (Thymus vulgaris) vem sendo explorado devido suas propriedades antimicrobianas (Gonçalves, et al, 2017). A alta volatilidade de seus componentes é um fator crítico que pode ser resolvido com o uso da técnica de microencapsulação (Fernandes et al, 2022).…”
Section: Introductionunclassified